Knowledge evolution within human urine recycling technological innovation system (TIS): Focus on technologies for recovering plant-essential nutrients. (15th December 2022) - Aliahmad, Abdulhamid; Harder, Robin; Simha, Prithvi; Vinnerås, Björn; McConville, Jennifer
Abstract: Adopting urine-recycling technologies can support a transition to circular nutrient management systems. Although these technologies have been developed since the 1990s, their large-scale implementation remains limited. From a technological innovation system (TIS) perspective, "knowledge development and diffusion" is a critical function in the development phase. Yet, available methods in the literature to evaluate this function are not standardized. Hence, this study aims to fill this literature gap by developing a novel multi-criteria framework for evaluating knowledge functions. Several characteristics of emerging technologies are reflected in the criteria, including the rate of growth, novelty, diffusion, and relationship to incumbent systems. The knowledge base was measured by bibliometric analysis of publications obtained from comprehensive mapping. Results showed that the rate of publications and knowledge diffusion increased sharply in 2011–2021 compared to 1990–2010. However, the function still has insufficiency in some criteria. The lack of innovation in scientific research and the diversification of technologies were found to be impediments. The analysis also identified the lock-in of conventional technologies and centralized infrastructures in terms of publication dominance as another impediment. For the TIS to be legitimate and to grow, more pilot-scale implementations at a higher level are recommended to demonstrate that the technology works in practice.